2017
DOI: 10.3389/fncel.2017.00110
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Ischemic Brain Injury in Neuroplastin 65-Deficient Mice Likely via Glutamate Excitotoxicity

Abstract: Cell adhesion molecules (CAMs) are involved in synaptic plasticity and neuronal survival in the adult brain. Neuroplastin 65 (Np65), one member of the immunoglobulin superfamily of CAMs, is brain-specific and highly expressed in rodent forebrain. The roles of Np65 in synaptic plasticity have been confirmed, however, whether Np65 affects neuronal survival remains unknown. To address this gap, we generated, to our knowledge, the first Np65 knockout (KO) mice. By occluding middle cerebral artery to perform ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…However, the NPTN-deficient rats could not complete the following experiments due to insufficient survival time after injecting PTZ. Previous studies also showed that the mice which was lack of Np65 (an isoform of NPTN) did not exhibit spontaneous epilepsy [ 61 , 62 ], but exhibited significant neurotoxicity in stroke models, which indicating that NPTN-deficient mice can exhibit significant E-I imbalance by receiving proper exogenous stimulation [ 61 ]. Since NPTN is not the only anchor protein of GABAaRs [ 22 ], simple deficiency of NPTN will not cause spontaneous seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the NPTN-deficient rats could not complete the following experiments due to insufficient survival time after injecting PTZ. Previous studies also showed that the mice which was lack of Np65 (an isoform of NPTN) did not exhibit spontaneous epilepsy [ 61 , 62 ], but exhibited significant neurotoxicity in stroke models, which indicating that NPTN-deficient mice can exhibit significant E-I imbalance by receiving proper exogenous stimulation [ 61 ]. Since NPTN is not the only anchor protein of GABAaRs [ 22 ], simple deficiency of NPTN will not cause spontaneous seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Ruth M. Empson et al found that NPTN reduced surface expression of AMPARs [ 23 ]. Yuhui Hu et al suggested that the vesicular glutamate transporter-1(VGluT1), and NMDARs were significantly increased in NPTN-KO mice [ 61 ]. Excessive accumulation of calcium ions in neurons is associated with seizures [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests much higher complexity of potential Np functions in vital cellular processes than initially foreseen. Additional observations suggested that Nps are related to nervous cell energy metabolism and tissue response to ischemic injury as follows: acting as chaperones of monocarboxylate transporter MCT2 [14]; being involved in tissue response following ischemic injury in rat forebrain [10]; ensuring hypothesized mechanisms of tissue recovery as Np-knockout (KO) mice have been found to be more susceptible to ischemic brain lesions [27].…”
Section: Neuroplastin Discovery Structure and Functionsmentioning
confidence: 99%
“…Vesicular glutamate transporter‐1 (VGLUT‐1) is widely expressed in the cerebral, cerebellar cortex, and hippocampus, and VGLUT1 provides approximately 80% of total vesicular glutamate uptake in the central nervous system (Danbolt, 2001). In a study in mice, it was reported that VGLUT1 expression increased on the 7th day of ischemic injury to reduce the increased glutamate in the forebrain after ischemia (Hu et al, 2017). Excess glutamate in the synaptic cleft is taken into the cell by excitatory amino acid transporters (EAAT) found in both neurons and glia (Danbolt, 2001).…”
Section: Introductionmentioning
confidence: 99%